Czechoslovak Subject Files
The files contain mostly newspaper clippings from western press sources, news agency releases but also brochures on Agriculture, Economic Conditions and Policy, Intellectual life, Population, Prisons and Youth. Of particular interest are files on Human Rights, Concentration Camps, Foreign Relations: Russia and Politics and Government. Accruals not expected